ANALISIS BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN MEMBELI KUE TALAM DURIAN DI RUMAH KUE VIERA JALAN MELATI KOTA PEKANBARU - Ananda Pratama; Ermy Tetty; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The purpose of this research are : 1) Analyze the marketing mix that affects consumers ' decision to buy Talam Durian cakes at the Viera Cake House on Melati street Pekanbaru city 2) To analyze the relationship between marketing mix to consumer decision to buy Talam Durian at the Viera Cake House on Melati street Pekanbaru city. The data analysis used is the marketing mix analysis. Consumer decision in making the purchase of Talam Durian cake by 7 (Seven) variable marketing mix IE product, price, location, promotion, person, physical means and process. Products with the category of